Correct the smile of a child by neuromuscular facilitation technique: An interesting case report - Aranha, Vencita Priyanka; Samuel, Asir John; Narkeesh, Kanimozhi (International Journal of Health Sciences, 2017)
Bell’s palsy (BP) in children is a rare case with no documented evidence regarding its rehabilitation management. Till date, individuals with BP are being treated with electrical stimulation are proportionately greater than other conventional means such as facial exercise and massage. These conventional modes of treatment have proved to have less incidence of synkinesis with more benefits. Here, we report a case of a 7-year-old boy diagnosed clinically to have right idiopathic facial nerve paralysis, who underwent 14 days of facial proprioceptive neuromuscular facilitation exercises along with facial therapeutic massage. Documented improvements in facial grading system reveal promising outcomes. Hence, we propose the above technique might improve the functional outcome in the children with BP.